Ehlers Danlos Syndrome: An Unusual Presentation You Need to Know about. (15th May 2013) - Karaa, Amel; Stoler, Joan M.
Abstract : The Ehlers Danlos syndromes (EDS) comprise a group of connective tissue disorders characterized by tissue fragility of the skin, ligaments, blood vessels and internal organs. Variable degrees of clinical severity and organ involvement are due to the molecular and biochemical heterogeneity of this group of disorders and have led to classification into well-characterized subtypes that are extending with the discovery of new genes and overlapping syndrome. Types include classical EDS (EDS I/II), hypermobility EDS (EDS III), vascular EDS (EDS IV), kyphoscoliosis EDS (EDS VI), arthrochalasia (EDS VIIA, B) and Dermatospraxis (EDS VIIC). Even to the well trained professional, the diagnosis of EDS remains a challenge due to overlapping symptoms and cases can remain without a well-defined classification. Life altering complications of this group of disorders include vascular and hollow organ rupture and ligamentous laxity leading to chronic dislocation with ensuing pain and long term disability. Patients initially present to the general practitioner who is expected to recognize the symptoms of EDS and to proceed with appropriate referral for definitive diagnosis and management to prevent devastating complications. In this paper, we describe a male with classical EDS complicated by devastating vascular and orthopedic events.